The Impact of Late Secondary Hyperparathyroidism on Mortality in COVID-19 Patients: A Longitudinal Study - Sima Hashemipour; Sabereh Afshar; Somaieh Kiani; Pouria Shahsavari; Milad Badri; Arefeh Ghobadi; Mohammad Reza Hadizadeh Khairkhahan (The Journal of Qazvin University of Medical Sciences, 2022)
Background: Adverse effects of high parathormone hormone (PTH) in critical illness have been described in some studies. Objective: The relationship between high PTH levels with mortality in hospitalized patients with COVID-19 was evaluated in the present study. Methods: A total of 123 patients were included in the study. The patients were evaluated in phase 1 (on admission) and phase 2 (days 4-6 of hospitalization). The patients were categorized into four groups based on the PTH status in both phases: normal PTH1/normal PTH2 (group 1), high PTH1/normal PTH2 (group 2), high PTH1/high PTH2 (group 3), and normal PTH1/high PTH2 (group 4). The multiple logistic regression analysis was performed to examine the independent association of late hyperparathyroidism with mortality. After excluding ineligible participants, 115 patients in phase 1 and 96 patients in phase 2 (days 4-6 of hospitalization) were evaluated. Findings: The level of phase 2 PTH in non-survivors was significantly higher than in survivors (57.5±40.9 pg/mL vs. 27.6±16.2 pg/mL, P=0.001). The mortality rate was significantly higher in high-PTH groups in phase 2 compared to normal-PTH groups in this phase (50% and 42.9% in groups 3 and 4 vs. 6.6% and 18.2% in PTH groups 1 and 2, respectively, P=0.007). Late hyperparathyroidism was associated with 11.4 times higher mortality risk (95% CI: 2.3-56.1, P=0.003). Conclusion: Late hyperparathyroidism remained a significant predictor of mortality after adjusting for the main PTH secretion modulators and disease severity. Late hyperparathyroidism is an independent and strong risk factor for mortality in COVID-19. Further studies are necessary to clarify the mechanisms involved.